2011
DOI: 10.1186/1556-276x-6-311
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the conversion of In2O3 into InN nanowires

Abstract: Straight In 2 O 3 nanowires (NWs) with diameters of 50 nm and lengths ≥2 μm have been grown on Si(001) via the wet oxidation of In at 850°C using Au as a catalyst. These exhibited clear peaks in the X-ray diffraction corresponding to the body centred cubic crystal structure of In 2 O 3 while the photoluminescence (PL) spectrum at 300 K consisted of two broad peaks, centred around 400 and 550 nm. The post-growth nitridation of In 2 O 3 NWs was systematically investigated by varying the nitridation temperature b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…No peaks related to Sn make their appearance despite the presence of H 2 . Finally we find that employing a two step temperature nitridation process involving NH 3 : 20% H 2 and slow ramp rates as listed in Table 1 was successfully achieved by employing the nitridation strategies described above [23,24]. The post-growth nitridation of b-Ga 2 O 3 and In 2 O 3 NWs proceeds via a reduction to Ga 2 O and In 2 O, respectively, which react with NH 3 .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…No peaks related to Sn make their appearance despite the presence of H 2 . Finally we find that employing a two step temperature nitridation process involving NH 3 : 20% H 2 and slow ramp rates as listed in Table 1 was successfully achieved by employing the nitridation strategies described above [23,24]. The post-growth nitridation of b-Ga 2 O 3 and In 2 O 3 NWs proceeds via a reduction to Ga 2 O and In 2 O, respectively, which react with NH 3 .…”
Section: Resultsmentioning
confidence: 92%
“…In addition we have grown and investigated the optical properties of metal oxide (MO) nanowires, i.e. SnO 2 , In 2 O 3 and b-Ga 2 O 3 [20][21][22] NWs and their conversion into nitrides via post-growth nitridation using NH 3 and H 2 [23,24]. We found that it is possible to obtain InN and GaN NWs via the postgrowth nitridation of In 2 O 3 and Ga 2 O 3 NWs, respectively, so here we have undertaken a systematic investigation into the nitridation of SnO 2 NWs in order to improve our understanding of Sn 3 N 4 and enable further investigations on its potential as a material for solar cell devices.…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxide (MO) semiconductor NWs are in particular attractive for the fabrication of sensors, solar cells, electronic and optoelectronic nanoscale devices. In the past we have investigated a broad range of MO NWs such as ZnO 1 In 2 O 3 2, 3 Ga 2 O 3 4 and SnO 2 NWs 5, 6. The latter are attractive since they may be grown with uniform diameters of 50 nms and lengths up to 100 µm by the reaction of Sn with O 2 on Au/Si(001) thereby avoiding the incorporation of other impurities such as C which is included during carbothermal reduction synthesis of MO NWs.…”
Section: Introductionmentioning
confidence: 99%
“…solar cells, especially as it is possible to tune their energy band gap over a wide range like for instance in InGaN [13]. Recently, we also demonstrated the conversion of In 2 O 3 [14] and Ga 2 O 3 NWs [15] into their respective nitrides, i.e. InN and GaN, using different post growth nitridation strategies including NH 3 and H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we have undertaken a systematic investigation into the post growth nitridation and conversion of ZnO NWs into Zn 3 N 2 NWs, thereby complementing our earlier investigations on the nitridation of other MO NWs [14,15]. ZnO NWs with diameters of 50 to 250 nm, lengths up to 10 μm and a hexagonal wurtzite crystal structure were obtained with a high yield and uniformity not only on ≈1 nm Au/Si(001) and 1 nm Au/quartz via reactive vapour transport, but also on plain Si(001) at 550°C.…”
Section: Introductionmentioning
confidence: 99%